My life - Clinton, Bill, 1946- (Arrow Books, 2005)
President Bill Clinton's My Life is the strikingly candid self-portrait of a world leader who decided in early life to devote his intellectual and political gifts, and his extraordinary capacity for hard work, to serving the people of America and the entire world population. It is the fullest, most concretely detailed, most nuanced account of a presidency ever written, and a testament to the positive impact that his work and his political ideals had on America and on the world. Here is the life of a great national and international figure, revealed with all his talents and contradictions. Filled with fascinating moments and insights, it is told openly, directly, in President Clinton's immediately recognisable voice. A fascinating journey through American politics, and one of the world's most famous politicians, and popular presidents.